Pengaruh Latihan Dribble Bola Basket Mini Terhadap Kemampuan Koordinasi Tangan Dan Mata Anak Tunagrahita - Slamet Raharjo; Irmantara Subagio (Departemen Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2026)
This study aims to determine the effect of mini-basketball dribbling training on eye-hand coordination in children with moderate intellectual disabilities in the SDLB Malang Regency. This study uses a one-group pretest-posttest design. The study sample consisted of students with moderate intellectual disabilities at the SDLB Widya Shantika Malang Regency. The sample selection in this study used purposive sampling, involving 6 children. Data collection techniques utilized a testing instrument, specifically a test measuring the distance a ball can be thrown by hand. Data were tested for normality using the Kolmogorov-Smirnov test and hypothesis testing using the paired sample t-test, assisted by the SPSS Statistics for Windows version 25 application. The data analysis technique used was the paired sample t-test with a significance level of α > 0.05. The results of this study indicate that mini basketball dribbling practice showed an improvement, but was not significant in terms of eye-hand coordination among children with moderate intellectual disabilities at the elementary school level at SLB Widya Shantika in Malang Regency. The statistical test results showed a significance value of 0.363. Since the significance value was > 0.05, the data was not significant. However, when comparing the average eye-hand coordination scores before the intervention (1.50) and after the intervention (1.83), the posttest average was higher than the pretest average, indicating an improvement in eye-hand coordination of 0.33.